The simplification of (-2 - 2i)( -4 + 6i) is 20 - 4i
SOLUTION:
In this particular question we have been asked to simplify the given equation containing complex numbers.
The given equation is:
(-2-2i)(-4+6i)
To simplify the equation we have to open the brackets and multiply.
Before we do that we need to know the value of i.
‘i’ is as complex number with a value of
and
has a value of -1
So now we can calculate the given expression as follows:
= (-2 - 2i)( -4 + 6i)
![\begin{array}{l}{=(-2 *-4)+(-2 * 6 i)+(-2 i *-4)+(-2 i * 6 i)} \\\\ {=8-12 i+8 i-12 i^(2)} \\\\ {=8-4 i-12 *-1} \\\\ {=8+12-4 i} \\\\ {=20-4 i}\end{array}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/2jdejmbkxc11bh7x6466ji1jb6bud5z6bd.png)
Therefore, the correct option is 20 - 4i.